2020
DOI: 10.1080/13658816.2020.1719109
|View full text |Cite
|
Sign up to set email alerts
|

Identifying what constitutes complexity perception of decision points during indoor route guidance

Abstract: To be able to design indoor wayfinding systems that adhere better to the needs of the users, user perception on complexity needs to be examined and linked to user characteristics and decision point characteristics. To identify how these characteristics influence perception, an online survey is executed in which participants had to indicate how complex they found a decision point, while interpreting a route instruction. The results show that complexity ratings depend both on user characteristics and on the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
2
15
3
1
Order By: Relevance
“…In the shallow spaces, on the other hand, it seems there was no noticeable variation in the navigation velocity influenced by the space syntax, so the participants mainly maintained a constant navigation velocity. This interpretation is in line with the findings from a study by De Cock et al [12], in which the turns in the convex spaces are perceived as more complex than the turns in the narrow corridors. This might furthermore explain why the navigation velocity at the infrastructural landmarks was significantly lower than in the objects category, since the former are mainly located in the convex spaces (mean MVD of this category = 6,19) and the latter in the narrow hallways (mean MVD of this category = 5,37).…”
Section: Building Layout and Architecturesupporting
confidence: 92%
See 3 more Smart Citations
“…In the shallow spaces, on the other hand, it seems there was no noticeable variation in the navigation velocity influenced by the space syntax, so the participants mainly maintained a constant navigation velocity. This interpretation is in line with the findings from a study by De Cock et al [12], in which the turns in the convex spaces are perceived as more complex than the turns in the narrow corridors. This might furthermore explain why the navigation velocity at the infrastructural landmarks was significantly lower than in the objects category, since the former are mainly located in the convex spaces (mean MVD of this category = 6,19) and the latter in the narrow hallways (mean MVD of this category = 5,37).…”
Section: Building Layout and Architecturesupporting
confidence: 92%
“…To conclude, this research has shown that wayfinding might be harder at the deep convex spaces than it is in the shallow convex spaces. This complies with the findings of other research on indoor wayfinding, whereby more integrated spaces with high visual access were rated as less complex [12,[38][39][40]. Despite the strong impact of player movement complexity, determined in the previous steps of this study, it can thus be said that decision point characteristics, landmarks, and building layout also seemed to have an important influence on indoor wayfinding in this case study.…”
Section: Building Layout and Architecturesupporting
confidence: 90%
See 2 more Smart Citations
“…120° instead of 360°) were used (Dalton, 2003;Meilinger, Franz & Bülthoff, 2012). It has been demonstrated that isovists may directly predict navigation behavior (Franz & Wiener, 2005;Meilinger et al, 2012), and that they correlate with perception of complex decision points (De Cock et al, 2020) and with human comprehension of enclosed spaces (Dosen & Ostwald, 2016). The size and shape of isovists even have subconscious effects on our everyday choices, such as choosing a table in a restaurant, where to wait to be recognized by a friend in a public space, which street to go down to avoid being mugged, or even which side of the bed to sleep on (Benedikt & McElhinney, 2019).…”
Section: Introductionmentioning
confidence: 99%